Organocatalytic synthesis of Pentafulvene derivatives and kinetic analysis of copper catalyzed 1,4-addition - Nouch, Ryan (2020)
Chapter 1 discloses a novel organocatalytic method for the synthesis of pentafulvenes bearing chiral pendant groups. Despite the widespread utility of pentafulvenes, synthetic methods towards them have not developed significantly since their initial discovery in 1900. More specifically, syntheses of pentafulvenes bearing pendant chiral groups are extremely uncommon. The primary aim of this work was to develop the asymmetric synthesis of pentafulvene 1.162a. Novel pentafulvene (±)-1.162a was observed to form in the pyrrolidine catalyzed reaction between 2-acetylbenzaldehyde (1.160a) and CpH. It was envisaged that an enantioselective variant of this reaction could help to furnish 1.162a as a single enantiomer, utilizing the fact that 1.162a was found to crystallize as a conglomerate. This resulted in the chiral amplification of scalemic mixtures of 1.162a to enantiopure 1.162a during crystallization. The reduction of enantiopure 1.162a to the corresponding CpH derivative could then be performed in a diastereoselective manner. This provided a novel, facile method to afford a structurally diverse library of chiral CpH derivatives.